(untitled) (Baghdad Science Journal, 2012)
The objective of this research was to investigate the effect of replacing fat(shortening) with different percentages of tahena on the quality properties (physiochemical and sensory ) of shortened cake.The percentages of moisture,protein ,fat and ash of cake increased significantly(p